The effects of tidal volume size and driving pressure levels on pulmonary complement activation: an observational study in critically ill patients - de Beer, Friso M.; Wieske, Luuk; van Mierlo, Gerard; Wouters, Diana; Zeerleder, Sacha; Bos, Lieuwe D.; Juffermans, Nicole P.; Schultz, Marcus J.; van der Poll, Tom; Lagrand, Wim K.; Horn, Janneke (Intensive care medicine experimental, 2020)
Background Mechanical ventilation can induce or even worsen lung injury, at least in part via overdistension caused by too large volumes or too high pressures. The complement system has been suggested to play a causative role in ventilator-induced lung injury. Aims and methods This was a single-center prospective study investigating associations between pulmonary levels of complement activation products and two ventilator settings, tidal volume ( V T ) and driving pressure (Δ P ), in critically ill patients under invasive ventilation. A miniature bronchoalveolar lavage (BAL) was performed for determination of pulmonary levels of C5a, C3b/c, and C4b/c. The primary endpoint was the correlation between BAL fluid (BALF) levels of C5a and V T and Δ P . Levels of complement activation products were also compared between patients with and without ARDS or with and without pneumonia. Results Seventy-two patients were included. Median time from start of invasive ventilation till BAL was 27 [19 to 34] hours. Median V T and ΔP before BAL were 6.7 [IQR 6.1 to 7.6] ml/kg predicted bodyweight (PBW) and 15 [IQR 11 to 18] cm H 2 O, respectively. BALF levels of C5a, C3b/c and C4b/c were neither different between patients with or without ARDS, nor between patients with or without pneumonia. BALF levels of C5a, and also C3b/c and C4b/c, did not correlate with V T and Δ P . Median BALF levels of C5a, C3b/c, and C4b/c, and the effects of V T and Δ P on those levels, were not different between patients with or without ARDS, and in patients with or without pneumonia. Conclusion In this cohort of critically ill patients under invasive ventilation, pulmonary levels of complement activation products were independent of the size of V T and the level of Δ P . The associations were not different for patients with ARDS or with pneumonia. Pulmonary complement activation does not seem to play a major role in VILI, and not even in lung injury per se, in critically ill patients under invasive ventilation.